Statistical dynamics of tropical wind in radiosonde data - T.-Y. Koh; Y. S. Djamil; C.-K. Teo (Atmospheric Chemistry and Physics, 2011)
Weibull distributions were fitted to wind speed data from radiosonde stations in the global tropics. A statistical theory of independent wind contributions was proposed to partially explain the shape parameter k obtained over Malay Peninsula and the wider Equatorial Monsoon Zone. This statistical dynamical underpinning provides some justification for using empirical Weibull fits to derive wind speed thresholds for monitoring data quality. The regionally adapted thresholds retain more useful data than conventional ones defined from taking the regional mean plus three standard deviations. The new approach is shown to eliminate reports of atypically strong wind over Malay Peninsula which may have escaped detection in quality control of global datasets as the latter has assumed a larger spread of wind speed. New scientific questions are raised in the pursuit of statistical dynamical understanding of meteorological variables in the tropics.